2011
DOI: 10.1111/j.1420-9101.2011.02249.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation ofSaccharomyces cerevisiaeto saline stress through laboratory evolution

Abstract: Most laboratory evolution studies that characterize evolutionary adaptation genomically focus on genetically simple traits that can be altered by one or few mutations. Such traits are important, but they are few compared with complex, polygenic traits influenced by many genes. We know much less about complex traits, and about the changes that occur in the genome and in gene expression during their evolutionary adaptation. Salt stress tolerance is such a trait. It is especially attractive for evolutionary studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 131 publications
4
120
1
1
Order By: Relevance
“…Differential selection across ploidy levels has been observed in different abiotic environments (e.g., Dhar et al 2011) and increased ploidy has been suggested to provide a selective advantage in adaptation to new environmental conditions (Pawlowska and Taylor 2004;Ma et al 2009). However, despite the strong selection pressure that is expected in serpentine soils and a report of possible influences of serpentine on the evolution of polyploids in K. arvensis (Kolář et al 2012), we did not find significant differentiation in genome size between the C. geophilum populations included in this study, suggesting that genetic and demographic processes are more important in shaping the genome size variation of this species than environmental selection in the form of home soil chemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential selection across ploidy levels has been observed in different abiotic environments (e.g., Dhar et al 2011) and increased ploidy has been suggested to provide a selective advantage in adaptation to new environmental conditions (Pawlowska and Taylor 2004;Ma et al 2009). However, despite the strong selection pressure that is expected in serpentine soils and a report of possible influences of serpentine on the evolution of polyploids in K. arvensis (Kolář et al 2012), we did not find significant differentiation in genome size between the C. geophilum populations included in this study, suggesting that genetic and demographic processes are more important in shaping the genome size variation of this species than environmental selection in the form of home soil chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Candida glabrata on the other hand is a haploid fungal species that displays frequent changes in its chromosome complement in relation with pathogenicity and a changing environment (Poláková et al 2009). Specific environmental factors that have been shown to affect fungal genome size include salt stress (Dhar et al 2011), fungicide treatments (Welker and Williams 1980), heat shock treatments (Hilton et al 1985), and host-pathogen interactions (Raffaele and Kamoun 2012).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…For instance, in E. coli, mutations have been identified in the proline ABC transporter gene proV (Dragosits et al, 2013;Winkler et al, 2014), and in the osmoprotectant biosynthesis genes otsBA (Stoebel et al, 2009). In yeast, mutations were found in the proton efflux pump gene pma1, the global transcriptional repressor gene cyc8 (Anderson et al, 2010) and the mot2 gene that has an unknown role in salt tolerance (Dhar et al, 2011). Here, we employ experimental evolution coupled with whole-genome whole-population sequencing and site-directed mutagenesis to discover and verify the functional genes conferring salt tolerance in an anaerobic environmental bacterium Desulfovibrio vulgaris.…”
Section: Introductionmentioning
confidence: 99%
“…Salt-stress tolerance is a polygenic trait especially attractive for evolutionary studies (Dhar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%